Superconductivity - Poole, Charles P. (Academic Press, 1995)
Superconductivity covers the nature of the phenomenon of superconductivity. The book discusses the fundamental principles of superconductivity; the essential features of the superconducting state-the phenomena of zero resistance and perfect diamagnetism; and the properties of the various classes of superconductors, including the organics, the buckministerfullerenes, and the precursors to the cuprates. The text also describes superconductivity from the viewpoint of thermodynamics and provides expressions for the free energy; the Ginzburg-Landau and BCS theories; and the structures of the high.